The Dynamics of Behavioural Economics and Its Influential Determinants - Ioffe, Mykhailo; Klimova, Inna; Petrukha, Nina (Journal of Posthumanism, 2025)
Relevance: Given the growing role of behavioural economics in shaping economic decisions under uncertainty, identifying factors that influence individuals’ economic behaviour is important for forecasting consumer trends and optimising public economic policy. Aim: The article aims to analyse the theoretical aspects of behavioural economics and investigate the impact of macroeconomic factors on the financial behaviour of economic entities in an unstable environment. Methods: In the course of the study, several general scientific methods of cognition were used, including synthesis of literature sources, comparative analysis, methods of systematisation and generalisation, as well as analysis of statistical data to form the initial data for further correlation and regression analysis to identify the relationships between dependent and independent variables and to form behavioural aspects of economic decisions through the impact of macroeconomic factors on the financial activity of economic entities. Results: The correlation analysis revealed a moderate positive relationship between deposits and loans (r = 0.642), indicating that savings and capital raising decisions are interdependent; a significant negative relationship between the unemployment rate and deposits (r = -0.930) and loans (r = -0.628); and a weak correlation between inflation and deposits (r = 0.063) and loans (r = 0.188). In contrast, further regression modelling of deposit activity showed that adding the unemployment rate to the model significantly increases its explanatory power (R2 = 0.909), confirming its significant impact on deposit volumes. Similarly, in the regression model of lending, including average wages significantly improved the predictive power (R2 = 0.77), indicating its important role in shaping lending activity. Conclusion: Considering cognitive and emotional factors in financial models is becoming a key element for making more accurate forecasts of economic entities’ financial activity, especially in conditions of instability; this opens up opportunities for improving strategies for the state regulation of economic entities’ behaviour to ensure rationality in their economic decision-making.